Les chants sacrés des Ursulines de Québec à l'époque de Marie Guyart - Courville, Louise (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

Colloquy/Débat: Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James (Canadian University Music Review, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.
Keywords: Canadian music; Careers; Composers; Composition; Music

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Quarante ans au cœur de l'Orchestre symphonique de Montréal - Lyse, Vézina (Varia, 2000)

Emma Albani - Vachon, Pierre (Éditions Lidec, 2000)
Biographie concise sur la carrière d'une illustre compatriote, Emma Lajeunesse dite Albani. Elle fut la première cantatrice québécoise à connaître une renommée internationale.

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)